(untitled) (Biological Sciences - PJSIR, 2024)
The bacteria producing proteases are important for the industries. The proteases are utilized commercially in leather, detergent, pharmaceutical and food industry. The proteases are hydrolytic enzymes which can degrade protein into peptides and amino acids. In leather industry proteases are employed to remove the redundant parts from the animal hide especially hairs to make fine quality of the products. The proteases also prove as green environmental approach. In present study a total of 40 bacterial isolates were recovered from the soil samples of the tannery and screened for proteolytic activity on casein ager plates, among them three isolates were selected with good activity. The morphological and biochemical characteristic features were used to identify the strains; the different conditions of the culture and medium were optimized to check the protease activity. The best proteolytic activity was observed at temperature of 37 °C, pH 8.5, 6% casein concentration as substrate and casein as nitrogen sources as well at 12 h of incubation. The maximum activities by SZ2, SZ1 and SZ3 observed 16.53U/mL, 8U/mL and 7.16U/mL, respectively. The goat skin was treated with proteases from these isolates, complete dehairing observed after 12 h of incubations. Present study was conducted to identify microbes from local tannery, to find out most efficient strain for protease production and to use these enzymes in leather industry.